Recent Trends in the Recurrence of North Atlantic Atmospheric Circulation Patterns. (12th February 2018) - Yiou, Pascal; Cattiaux, Julien; Ribes, Aurélien; Vautard, Robert; Vrac, Mathieu
Abstract : A few types of extreme climate events in the North Atlantic region, such as heatwaves, cold spells, or high cumulated precipitation, are connected to the recurrence of atmospheric circulation patterns. Understanding those extreme events requires assessing long-term trends of the atmospheric circulation. This paper presents a set of diagnostics of the intra- and interannual recurrence of atmospheric patterns. Those diagnostics are devised to detect trends in the stability of the circulation and the return period of atmospheric patterns. We detect significant emerging trends in the winter circulation, pointing towards a potential increased predictability. No such signal seems to emerge in the summer. We find that the winter trends in the dominating atmospheric patterns and their recurrences do not depend of the patterns themselves.